Optimization of nonlinear inelastic steel frames considering panel zones. (April 2020) - Ha, Manh-Hung; Vu, Quang-Viet; Truong, Viet-Hung
Highlights: An efficient method for optimizing nonlinear inelastic steel frames considering panel zones has been developed. An improvement of Different Evolution algorithm has been proposed. 3 nonlinear inelastic steel frames have been carried out to investigate the robustness of the proposed method. The design of panel zones has been considered for the first time in the optimization of steel frames. Abstract: In this article, an efficient methodology is developed to optimize nonlinear steel frames under several load combinations. For that purpose, inelastic advanced analyses of steel frames are performed using plastic hinge beam–column elements to reduce computational efforts. An improved differential evolution (DE) algorithm is utilized as a global optimizer to refine the solution accuracy and enhance the convergence speed. Compared to the conventional DE algorithm, this newly developed method provides four major improvements such as: (1) a new mutation strategy based on the p-best method; (2) the multi-comparison technique (MCT) to decrease the number of unnecessary objective function evaluations; (3) a promising individual method (PIM) to choose trial individuals; and (4) a trial matrix containing all evaluated individuals to avoid objective function evaluations of duplicate individuals. Furthermore, panel zones are taken account of optimum design for the first time. Doubler plates are designed to prevent panel-zone shear deformations. Three mid- to large-size steel frames considering several load combinations required by AISC-LRFD are considered. Five new and efficient meta-heuristic algorithms are employed for comparison.